Protection of Consumer Rights of Pertamax Users Against Fuel Adulting Practices (2018 – 2023) - Canisya Pradiani; Satino Satino (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Consumer protection under Indonesian law aims to guarantee the right to security, safety, comfort, and accurate information, as specified in Law Number 8 of 1999 concerning Consumer Protection. Allegations of adulteration of Pertamax by PT Pertamina Patra Niaga and related parties have resulted in losses for consumers and have reduced public confidence in the quality of national fuel. This research uses a qualitative normative legal approach by analyzing legislation, legal doctrine, and expert opinions regarding consumer rights and business actors' obligations. Supporting data from consumer complaint reports compiled by LBH Jakarta and CELIOS is used to a limited extent to strengthen the context of the problem. The results indicate that although the legal framework normatively regulates consumer rights protection, in practice there are still weaknesses in the supervision and fulfillment of business actors' responsibilities, particularly in the energy sector.